2021
DOI: 10.1111/plb.13344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc imbalance and salicylic acid co‐supply on Arabidopsis response to fungal pathogens with different lifestyles

Abstract: In higher plants, Zn nutritional imbalance can affect growth, physiology and response to stress, with effect variable depending on host-pathogen interaction. Mechanisms through which Zn operates are not yet well known. The hormone salicylic acid (SA) can affect plant ion uptake, transport and defence responses. Thus, in this study the impact of Zn imbalance and SA co-supply on severity of infection with the necrotrophic fungal pathogen B. cinerea or the biotroph G. cichoracearum was assessed in A. thaliana Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
0
3
0
1
Order By: Relevance
“…After the war, the central questions were, whether the groundwater in Mosul city was suitable for drinking and domestic use, whether was suitable for irrigation of vegetables and fruits, and whether the consumed was safe for humans, because increase in toxic substance levels and heavy metals levels in the soil severly affected the groundwater quality and thus had an impact on humans and agricultural crops (Kumar Sharma et al, 2007 ;Quaglia et al ,2022;Robins and Fergusson,2014 ) To date, the answers have mostly remained elusive, as the available studies have mainly covered periods of investigation before the war.…”
Section: During the Occupation Of Mosul City Bymentioning
confidence: 99%
“…After the war, the central questions were, whether the groundwater in Mosul city was suitable for drinking and domestic use, whether was suitable for irrigation of vegetables and fruits, and whether the consumed was safe for humans, because increase in toxic substance levels and heavy metals levels in the soil severly affected the groundwater quality and thus had an impact on humans and agricultural crops (Kumar Sharma et al, 2007 ;Quaglia et al ,2022;Robins and Fergusson,2014 ) To date, the answers have mostly remained elusive, as the available studies have mainly covered periods of investigation before the war.…”
Section: During the Occupation Of Mosul City Bymentioning
confidence: 99%
“…For the last few eras, the prevalence of heavy metals in soil has become a serious issue throughout the world which disturbs the physical, chemical, and biological features of soil with reduction in fertility and plant growth. , It has also been observed that a major cause of retarded plant growth is the industrial waste that chiefly contains lead, zinc, chromium, and cadmium which serve as the key elements behind elevated land pollution. , Among these metals, zinc as a loaded nutrient in the soil causes decline in the plant biomass, gaseous exchange, chlorophyll contents, and nutrient absorptive capacity, causing alteration in cellular structures. In the previous reports, it has been observed that heavy-metal stress has shown negative impacts on plants’ vital cellular components and functions such as DNA damage, deformation of plant cells, and difference in cellular redox homeostasis, phytohormone contents, biomass, and yield. In another report, zinc has shown negative effects including phototoxicity, modulation in abiotic response and physiological parameters, reducing photosynthetic pigment concentration, and reduction in root activity of wheat and other plants. Although plants have their own defense system against heavy-metal stress to resist the change by cellular exudates, membrane integrity, activating heat shock proteins, metallothioneins, and organic acid within certain limits. , But, in the case of accumulation of heavy metals beyond a threshold and traditional strategies such as fertilizers, fungicides, insecticides, pesticides, use of dietaryfibers, and chelating agents are considered inadequate for coping with heavy-metal stress. Therefore, an exciting nanotechnological method of introducing nanomaterials has revolutionized the process of reducing metal stress to a great extent by absorbed heavy metals, reducing stress and enhancing the plant growth without any lethal effects. Nanotechnology is an emerging technique that is recounting its role in the agricultural field .…”
Section: Introductionmentioning
confidence: 99%
“… 17 19 In another report, zinc has shown negative effects including phototoxicity, modulation in abiotic response and physiological parameters, reducing photosynthetic pigment concentration, and reduction in root activity of wheat and other plants. 20 23 Although plants have their own defense system against heavy-metal stress to resist the change by cellular exudates, membrane integrity, activating heat shock proteins, metallothioneins, and organic acid within certain limits. 24 , 25 But, in the case of accumulation of heavy metals beyond a threshold and traditional strategies such as fertilizers, fungicides, insecticides, pesticides, use of dietaryfibers, and chelating agents are considered inadequate for coping with heavy-metal stress.…”
Section: Introductionmentioning
confidence: 99%
“…Pe lângă influența pozitivă a lor aspra productivității plantelor, s-a documentat şi faptul că acești bioferilizatori manifestă acţiune de protecție a plantelor contra maladiilor şi dăunătorilor (Loffredo et al, 2007;El-Ghamry et al, 2009). Recent s-a raportat că aplicarea sărurilor anorganice reprezintă instrumente fezabile în controlul maladiilor la plantele agricole în sistemul de producere convențional și organic (Quaglia et al, 2022). Un rol deosebit în acest aspect îl are microelementul zinc (Deliopoulos et al, 2010).…”
unclassified